The Transfer of Intellectual Property Rights as Object of Fiduciary Guarantee - Anis Mashdurohatun; Gunarto Gunarto; Adhi Budi Susilo (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
The transfer in Intellectual Property Rights (IPR)